Different levels of dietary DL-? tocopheryl acetate modulate the antioxidant defence system in the hepatopancreas, gills and muscles of the freshwater crayfish, Astacus teptodactylus (Eschscholtz, 1823) - Beytut, Ebru; Barim, Ozden; Kamiloglu, N. Nabil (My University, 2009)
This experiment was conducted to study the effects of different levels of dietary DL-? tocopheryl acetate on Lipid Peroxidation (LPO) as Malondialdehyde (MDA) and on the antioxidant defence system in the gills, hepatopancreas and muscles of the freshwater crayfish, Astacus leptodactylus. Crayfish were fed 2% of their total wet weight with vitamin E supplemented diets or a control diet, daily for 122 days. The vitamin E contents of the control diet and of the experiment 1 (E100), 2 (E600) and 3 (E1200) diets, were 66, 100, 600 and 1200 mg kg-1, respectively, on a dry weight basis. The activities of Superoxide Dismutase (SOD), Catalase (CAT) and Glutathione Peroxidase (GSH-Px) and levels of reduced Glutathione (GSH) and MDA were measured in the hepatopancreas, gills and muscles of the freshwater crayfish, Astacus leptodactylus. The results of the experiment indicated that vitamin E inhibited LPO at the hepatopancreas in a comparatively lower dose than in the gills and muscles. SOD activity decreased significantly in the gills and muscles of the crayfish fed with supplemented diets, but in the hepatopancreas a decrease was observed only in response to the higher doses of vitamin E (600 and 1200 mg kg-1 feed). CAT activity was reduced significantly in the gills and muscles but not in the hepatopancreas. While GSH-PX activity was significantly elevated in the hepatopancreas by vitamin E, its activity remained unaltered in the gills and muscles. The GSH content of the gills, hepatopancreas and muscles was substantially elevated in the vitamin E supplemented crayfish. Thus, the findings of the present investigation suggest that dietary vitamin E is capable of reducing LPO level and modulating the antioxidant defence system in gills, hepatopancreas and muscles. Nevertheless, the response is highly tissue specific. Moreover, the highest doses of vitamin E (600 and 1200 mg kg-1 feed) did not provide much additional protection in any of the tissues. © Medwell Journals, 2009.
Keywords: Antioxidant enzyme; Crayfish; Gills; Hepatopancreas; Lipid peroxidation; Muscle; Vitamin E